Ganoderma lucidum Spore Powder Alleviates Metabolic-Associated Fatty Liver Disease by Improving Lipid Accumulation and Oxidative Stress via Autophagy - Yuxuan Zhang; Jiali Zhou; Lan Yang; Hang Xiao; Dongbo Liu; Xincong Kang (Antioxidants)
Lipid accumulation and oxidative stress, which could be improved by autophagy, are the “hits” of metabolic-associated fatty liver disease (MAFLD). Ganoderma lucidum spore powder (GLSP) has the effect of improving liver function. However, there are few reports about its effects on and mechanisms impacting MAFLD alleviation. This study investigated the effect of GLSP on hepatic lipid accumulation and oxidative stress and explored the role that autophagy played in this effect. The results showed that GLSP effectively reduced lipid accumulation and activated autophagy in the livers of mice with high-fat-diet-induced disease and palmitic acid-induced hepatocytes. GLSP reduced the lipid accumulation by reducing lipogenesis and promoting lipid oxidation in HepG2 cells. It decreased the production of ROS, increased the activity of SOD and CAT, and improved the mitochondrial membrane potential via the Keap1/Nrf2 pathway. The alleviating effects of GLSP on the lipid accumulation and oxidative stress was reversed by 3-methyladenine (3-MA), an autophagy inhibitor. GLSP activated autophagy via the AMPK pathway in HepG2 cells. In conclusion, GLSP could attenuate MAFLD by the improvement of lipid accumulation and oxidative stress via autophagy. This paper is the first to report the improvement of MAFLD through autophagy promotion. It will shed novel light on the discovery of therapeutic strategies targeting autophagy for MAFLD.